Ligation of the hypogastric arteries in cervical cancer - Valdivia, Eduardo (2015)
There in obstetric and gynecological practice, various pathological conditions that determine copious vaginal or cervical bleeding body; which they are very difficult to control by conventional methods: utero-vaginal tamponade, cervical-vaginal suture, use of coagulants, repeated blood transfusions, etc., and ponene endangered the lives of these patients. In the case of cervical cancer, these hemorrhages are frequent and severe and persistent, diseased condition and exasperating for these delicate situations because routine therapeutic approach always fails. As there are numerous cases of cervix, however no radiation therapy, blood cancer continue to lose, we have meditated on various aspects of the problem.